Anxiety and depression in patients with giant cell arteritis - Martinho, Joana Martins (2023)
Objectives To compare the prevalence of anxiety and depression in patients with GCA with that in the general population, using the Hospital Anxiety and Depression Scale (HADS), and to identify independent predictors of these psychiatric manifestations in patients with GCA.Methods We conducted a cross-sectional study including all patients diagnosed with GCA followed during 1 year in a vasculitis outpatient clinic. The HADS and 36-item Short Form (SF-36) questionnaires were prospectively collected. Patients' HADS results were compared with an age- and gender-matched control group. HADS anxiety (HADS-A) and HADS depression (HADS-D) scores between 8 and 10 defined possible anxiety and depression and >= 11 defined probable anxiety and depression, respectively.Results We included 72 patients and 288 controls. Compared with controls, patients with GCA had a statistically significant higher prevalence of HADS-A >= 8 (48.6% vs 26.4%), HADS-A >= 11 (30.6% vs 12.2%) and HADS-D >= 11 (33.3% vs 18.1%). GCA was an independent predictor of HADS-A >= 8 [odds ratio (OR) 3.3 (95% CI 1.9, 5.9)], HADS-A >= 11 [OR 3.8 (95% CI 2.0, 7.4)] and HADS-D >= 11 [OR 2.6 (95% CI 1.4, 4.7)]. Among patients with GCA, a negative correlation was observed between HADS-A/D and SF-36 mental health scores (r = -0.780 and r = -0.742, respectively). Glucocorticoid therapy was a predictor of HADS-A >= 8 [OR 10.4 (95% CI 1.2, 94.2)] and older age of HADS-D >= 8 [OR 1.2 (95% CI 1.1, 1.3)] and HADS-D >= 11 [OR 1.1 (95% CI 1.0, 1.2)].Conclusions Compared with the general population, patients with GCA have a higher prevalence of anxiety and depression and GCA is an independent predictor of these symptoms. Glucocorticoid treatment and older age are predictors of anxiety and depression, respectively, in patients with GCA. What does this mean for patients?Giant cell arteritis (GCA) is a condition that causes inflammation of the arteries, most frequently in the head and neck. It affects predominantly the elderly and can potentially lead to stroke and blindness. Both GCA-related symptoms and treatment with glucocorticoids can impact mental health. We compared the prevalence of anxiety and depression in individuals with GCA with that of the general population using the Hospital Anxiety and Depression Scale (HADS). We found that GCA was an important contributor to a higher prevalence of anxiety and depression in this group compared with the general population. We also explored which aspects contributed the most to anxiety and depression in people with GCA. We found that treatment with glucocorticoids was a predictor for anxiety and older age was a predictor for both anxiety and depression. Moreover, we described a negative correlation between anxiety/depression scores and quality of life among people with GCA, which suggests an impact of mental health on overall well-being. These findings highlight the burden of anxiety and depression in GCA, emphasizing the need for awareness and physician attention to mental health in this population in order to improve overall care and elevate the quality of life for individuals with GCA.